The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12875-021-01552-3
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and visions for managing pain-related insomnia in primary care using the hybrid CBT approach: a small-scale qualitative interview study with GPs, nurses, and practice managers

Abstract: Background Chronic pain and insomnia have a complex, bidirectional relationship – addressing sleep complaints alongside pain may be key to alleviating patient-reported distress and disability. Healthcare professionals have consistently reported wanting to offer psychologically informed chronic pain management at the primary care level. Research in secondary care has demonstrated good treatment efficacy of hybrid CBT for chronic pain and insomnia. However, primary care is typically the main poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Access to behavioral providers with specialization in behavioral pain or headache treatments can be challenging, particularly in rural settings [ 40 ]. Therefore, patients may face limited options in behavioral treatment providers, resulting in limited behavioral treatment strategies that may not adequately address their specific treatment needs [ 41 , 42 ]. Recent studies have observed greater use of telemedicine for patients who receive specialty pain services in rural populations (12%) compared to urban patients (3%) [ 43 ].…”
Section: Mitigating Barriers and Improving Access To Carementioning
confidence: 99%
“…Access to behavioral providers with specialization in behavioral pain or headache treatments can be challenging, particularly in rural settings [ 40 ]. Therefore, patients may face limited options in behavioral treatment providers, resulting in limited behavioral treatment strategies that may not adequately address their specific treatment needs [ 41 , 42 ]. Recent studies have observed greater use of telemedicine for patients who receive specialty pain services in rural populations (12%) compared to urban patients (3%) [ 43 ].…”
Section: Mitigating Barriers and Improving Access To Carementioning
confidence: 99%